Answer:
![f(x)=x^3-7x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eyraxmd3klck6bsozjjj7cspjau9xlu2g7.png)
Explanation:
If x = 3 is a root of a polynomial f(x), then x - 3 is a factor of this polynomial.
If x = -2 is a zero of a polynomial function f(x), then f(-2) = 0 and x - (-2) = x + 2 is a factor of f(x).
If x = -1 is an x-intercept of the function, then y = 0 and x - (-1) = x + 1 is also a factor of the function f(x).
Therefore, the polynomial expression is
![f(x)=(x-3)(x+2)(x+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5ipnhd4881xxgzy5qb8pjuiuom7zr6h8qe.png)
In standard form:
![f(x)=(x-3)(x^2+2x+x+2)=(x-3)(x^2+3x+2)=x^3+3x^2+2x-3x^2-9x-6=x^3-7x-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w1l2p1ovou1oi8t8ciwnqvqim7fr0urvfy.png)